2002
DOI: 10.1016/s1010-7940(02)00272-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after surgical correction of atrioventricular septal defects

Abstract: In patients with AVSD of various morphologies closure of the left AV valve cleft significantly improves outcome without affecting the need for reoperation. Risk factors for early and late death (multivariate analysis) were a pulmonary/aortic pressure ratio >0.7 and the occurrence of any complication after surgery. The concept of an early surgical AVSD correction before an increase in pulmonary vascular resistance and AV valve deformations occur would represent a better surgical option than a late correction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 13 publications
4
55
1
5
Order By: Relevance
“…42 Certain factors are associated with worse outcomes from congenital heart defects, including the type and complexity of the malformation, associated extracardiac anomalies and congestive heart failure. [203][204][205][206][207][208][209][210][211] Children born with congenital heart defects have a higher incidence of neurological abnormalities, including microcephaly, hypotonia, hypertonia, seizures, feeding difficulties and lethargy in the newborn period, 173,175 and these do not appear to be predicted by difficulties at birth, such as birth asphyxia. 164,166,212 Preoperative cerebral infarctions have been noted in 4% of children with congenital heart defects and are associated with subsequent abnormal neurological development.…”
Section: Antenatal and Perinatal Factorsmentioning
confidence: 99%
“…42 Certain factors are associated with worse outcomes from congenital heart defects, including the type and complexity of the malformation, associated extracardiac anomalies and congestive heart failure. [203][204][205][206][207][208][209][210][211] Children born with congenital heart defects have a higher incidence of neurological abnormalities, including microcephaly, hypotonia, hypertonia, seizures, feeding difficulties and lethargy in the newborn period, 173,175 and these do not appear to be predicted by difficulties at birth, such as birth asphyxia. 164,166,212 Preoperative cerebral infarctions have been noted in 4% of children with congenital heart defects and are associated with subsequent abnormal neurological development.…”
Section: Antenatal and Perinatal Factorsmentioning
confidence: 99%
“…During the follow-up control, 3 patients underwent pacemaker explantation (2 patients recovered and had sinus rhythm, and 1 patient had heart transplantation), and another 3 patients required permanent pacemaker implantation, so that at the last follow-up control, there were 6 patients (5.7%) with permanent pacemaker due to complete AV-block. Böning et al reported 7.4% (52). The tendency for pacemaker implantation was significantly higher in group ND (14.3%) compared with group D (1.4%).…”
Section: Complete Av-block and Pacemaker Implantationmentioning
confidence: 91%
“…The only risk factor in this patient was preoperative pulmonary hypertension. Böning et al (52) reported that preoperative pulmonary hypertension was a risk factor for early mortality and recommended early surgical repair of AVSD, as delayed timing of surgery rather results in further elevation of pulmonary vascular resistance and fixed pulmonary hypertension. He reported also that the diagnosis of a complete AVSD, ECC more than 110 minutes, two-patch technique and ommittance of cleft closure as a specific risk factors for mortality.…”
Section: Survival and Mortalitymentioning
confidence: 99%
“…The incidence of LAVVR after surgical repair of AVSD ranges between 6 and 20 per cent. 4 As a consequence of the incompetent valve and low cardiac output syndrome following the operation and cardiopulmonary bypass, JL required ventilation and inotrope treatment in the immediate postoperative period.…”
Section: Case Historymentioning
confidence: 99%